Kewarisan Beda Agama (Studi Pandangan Muaz bin Jabal) - Riyanta, Riyanta (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Genealogy relationship to every aspect of life is a link for  a  generation  to  the  next  one.  The  continuity  of  generation needs the preparation and supply, materially or immaterially, in order to be able to exist and survive. Al-Qur‘an even suggested Moslem not to leave the weak generation. Therefore, genealogy relationship  was  believed  as  a  main  cause  of  inheritance transition from the dead to the heir. The problem appears when the Moslem has to bequeath to non Moslem. Al-Qur‘an does not explain  it,  even  the  tradition  forbade  the  interreligious inheritance,  whereas  the  social  context  demands  to  treat  the other way. The dialectic between law and social demand became a big problem to the Islamic law of inheritance.  The problem  of interreligious  inheritance  appeared  when  the  relationship between  Moslem  and  non  Moslem  was  re-discussed  by  some social groups. Moreover, it became attention of Moslem thinkers since its formation, such as Mua? bin Jabal. His decision to share the  inheritance  from  Moslem  to  non  Moslem  is  an  innovation that is needed to appreciate. He braves  to find another way  by ignoring  the  textual  law  towards  the  contextual  law  without leaving the essence of shariah. Besides it is for human benefit, it is also for implementing uptodate Islamic law.